Adherence to a Mediterranean diet and cognitive function in the Age‐Related Eye Disease Studies 1 & 2. Issue 6 (13th April 2020) - Keenan, Tiarnán D.; Agrón, Elvira; Mares, Julie A.; Clemons, Traci E.; van Asten, Freekje; Swaroop, Anand; Chew, Emily Y.; ,
Abstract: Introduction: The objective was to determine whether closer adherence to the alternative Mediterranean Diet (aMED) was associated with altered cognitive function. Methods: Observational analyses of participants (n = 7, 756) enrolled in two randomized trials of nutritional supplements for age‐related macular degeneration: Age‐Related Eye Disease Study (AREDS) and AREDS2. Results: Odds ratios for cognitive impairment, in aMED tertile 3 (vs 1), were 0.36 ( P  = .0001) for Modified Mini‐Mental State (<80) and 0.56 ( P  = .001) for composite score in AREDS, and 0.56 for Telephone Interview Cognitive Status‐Modified (<30) and 0.48 for composite score (each P  < .0001) in AREDS2. Fish intake was associated with higher cognitive function. In AREDS2, rate of cognitive decline over 5 to 10 years was not significantly different by aMED but was significantly slower ( P  = .019) with higher fish intake. Discussion: Closer Mediterranean diet adherence was associated with lower risk of cognitive impairment but not slower decline in cognitive function. Apolipoprotein E ( APOE ) haplotype did not influence these relationships.